2015
DOI: 10.1038/cmi.2015.86
|View full text |Cite
|
Sign up to set email alerts
|

The modulation of co-stimulatory molecules by circulating exosomes in primary biliary cirrhosis

Abstract: Exosomes are nanoparticles of endocytic origin, secreted by a myriad of cell populations that are attracting increased attention by virtue of their ability to modulate cell-to-cell communications. They are also attracting attention in a variety of immunological issues, including autoimmunity and, in particular, their ability to regulate cytokine and chemokine activation. Primary biliary cirrhosis (PBC) is considered a model autoimmune disease, which has a highly focused cytotoxic response against biliary epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 63 publications
0
37
0
Order By: Relevance
“…Epigenetic Change(s) Consequences PBC DNA demethylation of gene promoter of CXCR3 in X chromosome of CD4 + T lymphocytes [35] DNA demethylation of multiple other gene promoters in X chromosome of CD4 + , CD8 + and CD14 + T lymphocytes [35] MiR-451a and miR-642a-3p increased [187] Demethylation correlates inversely with CXCR3 expression [35] CXCR3 orchestrates immune and NK cell migration to injury site [185,186] MiRNAs affect immune regulation [187] PBC progression may result [35] PSC 21 miRNAs distinguish PSC [103] 33 miRNAs distinguish CAC [103] MiR-200c principal marker of PSC [103] MiR-222, 483-5p upregulated in CAC [103] Aberrant methylation of CAC genes [191] Uncertain pathogenic effects [103] Possible biomarkers for PSC, CAC [190] NAFLD Differential methylation of 9 genes [192] Disrupted insulin signalling and metabolism [192] 46 miRNAs differentiated in NASH [104,128] MiR-34a and miR-146b upregulated [104,128] Downregulated miR-122 affects lipids [104] Bariatric surgery reverses some changes [192] Weight loss increases gene methylation [193] Metabolic pathways altered by gene methylation and miRNAs [104,192] Weight reduction may reverse some epigenetic changes [192,193] AIH MiR-21 increased in Japanese patients [44] MiR-21 and miR-122 correlate with ALT [44] Low miR-21 and miR-122 in cirrhosis [44] MiR-21 targets PDCD4 gene [44,194] MiR-122 increases INF-1 production [196] Vitamin D deficiency alters VDRE effects on gene activity [215,…”
Section: Liver Diseasementioning
confidence: 99%
“…Epigenetic Change(s) Consequences PBC DNA demethylation of gene promoter of CXCR3 in X chromosome of CD4 + T lymphocytes [35] DNA demethylation of multiple other gene promoters in X chromosome of CD4 + , CD8 + and CD14 + T lymphocytes [35] MiR-451a and miR-642a-3p increased [187] Demethylation correlates inversely with CXCR3 expression [35] CXCR3 orchestrates immune and NK cell migration to injury site [185,186] MiRNAs affect immune regulation [187] PBC progression may result [35] PSC 21 miRNAs distinguish PSC [103] 33 miRNAs distinguish CAC [103] MiR-200c principal marker of PSC [103] MiR-222, 483-5p upregulated in CAC [103] Aberrant methylation of CAC genes [191] Uncertain pathogenic effects [103] Possible biomarkers for PSC, CAC [190] NAFLD Differential methylation of 9 genes [192] Disrupted insulin signalling and metabolism [192] 46 miRNAs differentiated in NASH [104,128] MiR-34a and miR-146b upregulated [104,128] Downregulated miR-122 affects lipids [104] Bariatric surgery reverses some changes [192] Weight loss increases gene methylation [193] Metabolic pathways altered by gene methylation and miRNAs [104,192] Weight reduction may reverse some epigenetic changes [192,193] AIH MiR-21 increased in Japanese patients [44] MiR-21 and miR-122 correlate with ALT [44] Low miR-21 and miR-122 in cirrhosis [44] MiR-21 targets PDCD4 gene [44,194] MiR-122 increases INF-1 production [196] Vitamin D deficiency alters VDRE effects on gene activity [215,…”
Section: Liver Diseasementioning
confidence: 99%
“…A s with most autoimmune diseases, primary biliary cholangitis (PBC) is female-predominant and has a long latency period between detection of autoantibodies and the clinical appearance of immunopathology. (1)(2)(3)(4) Although there are clearly major defects in adaptive immunity, including dysregulation of multiple T-cell and B-cell pathways, (5)(6)(7)(8)(9)(10)(11) there is significant evidence for the role of innate immunity in modulating and perhaps even initiating disease activity. (12)(13)(14)(15)(16)(17) Indeed, we have proposed that PBC is a multihit disease involving independent but overlapping immune path-ways that interact at different stages of disease activity, ultimately leading to the clinical entity of severe portal inflammation with potential cirrhosis.…”
Section: See Editorial On Page 1024mentioning
confidence: 99%
“…Other studies investigating PBC and liver fibrosis found that miR‐451a and miR‐642a‐3p were present at significantly higher levels in exosomes from patients with PBC compared to healthy controls and a progressive increase in circulating exosomal CCN2 was present in experimental fibrosis …”
Section: Exosomes As Novel Biomarkers Of Liver Diseasesmentioning
confidence: 93%
“…Therefore, exosomes may promote the progression of cirrhosis and other liver diseases with portal hypertension by inducing LSEC dysfunction. Furthermore, Tomiyama et al found that circulating exosomes from patients with primary biliary cirrhosis (PBC) selectively induced expression of co‐stimulatory molecules in different subsets of antigen‐presenting cells . This alteration may be involved in the pathogenesis of PBC and other autoimmune liver diseases.…”
Section: Exosomes In Liver Diseasesmentioning
confidence: 99%